SCABIES RISK FACTORS IN PATIENTS WITH MENTAL DISORDERS AND THE LONG-TERM TREATMENT OPTIONS IN INDONESIA - Astiyani, Roro Flaviana Bayu; Harioputro, Dhani Redhono; Susilo, R. Satriyo Budhi; Sumandjar, Tatar (Prosiding University Research Colloquium, 2024)
Scabies is still common in Indonesia, although the national prevalence of scabies cannot yet be explained. This study was conducted to assess the prevalence of scabies and risk factors in patients with mental disorders. The patients in this study were patients who received treatment at a mental hospital for scabies infection (n=94) from January 2022 to August 2023. There were 53 male patients (56.38%). There were 41 female patients (43.61%). The patients consisted of 35 patients who had previously been treated at a rehabilitation center (37.23%) and 59 patients who had previously been treated at home (62.76%). A cross-sectional analytical study showed that male patients previously treated at home were more likely to experience scabies attacks. The hospital develops scabies infection control guidelines, provides patient therapy with scabicides, and performs skin examinations on inpatients upon admission. Infection control teams should be aware that scabies can cause outbreaks. Insufficient screening is a risk factor for scabies infection entry to hospital. So preventive action against scabies, such as examining patients when they enter the hospital and treating all suspicious patients, are effective in preventing the infection of scabies.